Secure dynamic bits standard scheme in private cloud environment. Issue 3 (3rd October 2022) - Gagged, Ghanshyam; Jaishakti, S.M.
Cloud computing is progressively prevalent prototype for retrieving the resources. This paper suggests secure dynamic bit's standard (SDES) algorithm for transferring the data among Cloud Service Provider (CSP), Data Provider (DP), and Data User (DU). Once the data provider uploads files, it automatically uploaded to a local upload folder. Then, a process of encryption is initiated using SDES algorithm; the encryption time taken was 0.003 seconds and this encrypted file is uploaded into Dropbox. Before uploading the file into Dropbox, an auto resource allocation process is initiated, cloud service provider can able to decide whether the data provider file is approved or rejected. If approved those files are visible to the data users, otherwise, the files are blocked. To download the files, the data user is utilised to send the private key request to the cloud service provider then only data user can be able to download the files.